The Differential Effects of Augmented Reality and Product Presentation Strategies on Brand Recall: An Embodied Cognition Perspective - Liying Zhou; Limin Niu; Taiyang Zhao (Journal of Theoretical and Applied Electronic Commerce Research)
As augmented reality (AR) technology becomes more prevalent in marketing, its impact on consumer memory processes, particularly brand recall, remains underexplored. This study primarily employs an empirical research method, using two lab experiments to examine the interaction between product presentation formats (AR vs. non-AR) and presentation strategies (separate vs. collocation) in brand recall. Across two experiments, we showed that AR enhances brand recall only in collocation presentations, where multiple products are displayed together, but not in separate presentations of individual products. In single-product contexts, AR formats do not demonstrate a significant advantage over non-AR formats. These findings suggest that AR’s effectiveness is contingent on presentation strategy, highlighting the contextual boundaries of AR’s utility in influencing consumer memory. By integrating embodied cognition theory with associative network theory, this research advances our understanding of how immersive technologies shape brand recall, offering strategic insights for marketers seeking to leverage AR in diverse product presentation scenarios.